Effect of high hydrostatic pressure processing on rheological and textural properties of probiotic low-fat yogurt fermented by different starter cultures - Penna, A. L. B.; Gurram, Subbarao; Barbosa-Canovas, G. V. (Blackwell Publishing, 2006)
The effect of milk processing on rheological and textural properties of probiotic low-fat yogurt (fermented by two different starter cultures) was studied. Skim milk fortified with skim milk powder was subjected to three treatments: (1) thermal treatment at 85C for 30 min; (2) high hydrostatic pressure (HHP) at 676 MPa for 5 min; and (3) combined treatments of HHP (676 MPa for 5 min) and heat (85C for 30 min). The processed milk was fermented using two different starter cultures containing Streptococcus thermophilus, Lactobacillus delbrueckii ssp. bulgaricus, Lactobacillus acidophilus and Bifidobacterium longum at inoculation rates of 0.1 and 0.2%. Rheological parameters were determined and a texture profile analysis was carried out. Yogurts presented different rheological behaviors according to the treatment used, which could be attributed to structural phenomena. The combined HHP and heat treatment of milks resulted in yogurt gels with higher consistency index values than gels obtained from thermally treated milk. The type of starter culture and inoculation rate, providing different fermentation pathways, also affected the consistency index and textural properties significantly. The combined HHP and heat treatment of milks before fermentation, and an inoculation rate of 0.1% (for both cultures), led to desirable rheological and textural properties in yogurt, which presented a creamy and thick consistency that does not require the addition of stabilizers.